Molecular Vibration and Physicochemical Performance of Proton-Conducting Solid Polymer Electrolyte Membrane based on CMC/PVA/CH3COONH4 - Ndruru, Sun Theo Constan Lotebulo; Rachmadhanti, Elvira Nur; Fridarima, Shanny; Berghuis, Nila Tanyela; Prasetyo, Ridho; Yulianti, Evi; Hayati, Atika Trisna; Adriana, Risda; Siregar, Rabiyatul Adawiyah; Sofyan, Muhammad Ihsan; Sampora, Yulianti; Annas, Dicky; Madiabu, Muhammad Jihad (Universitas Jenderal Soedirman, 2024)
This work studied examined the influence of ammonium acetate (CH3COONH4) on CMC/PVA-based solid polymer electrolyte (SPE) membranes, focusing on molecular vibration, proton conductivity, and physicochemical properties. SPE membranes were prepared via the casting solution method with varying CH3COONH4 concentrations to determine the optimal proton conductivity. Various characterizations, including FTIR, EIS, XRD, and TGA, were performed. The optimal membrane condition was achieved with 10 wt-% CH3COONH4 in the CMC/PVA (80/20) blend, yielding proton conductivity of 3.93×10⁻⁴ S/cm and favorable mechanical, thermal, and crystallinity properties, making it suitable for proton-conducting polymer applications. Keywords: ammonium acetate, carboxymethyl cellulose, ionic conductivity, poly(vinyl alcohol), proton battery, solid electrolyte membrane